Parámetros Reproductivos del Ganado Mestizo Lechero de la Parroquia Mulaló - Álvarez Reisancho, Geovanny Cesar (2019)
The objective of this project is the characterization of the reproductive parameters of the mestizo dairy cattle at Mulaló Parish as a contribution to the conservation, maintenance and genetic improvement of the bovine species. The survey was applied to 100 owners of mongrel cattle, considering the general data on the reproductive behavior of small and medium milk producers in the cattle ranch, 145 female bovines were selected. The reproductive variables (reproductive indexes, reproductive problems, and veterinary attention) were evaluated. The data obtained were subjected to detailed design, and a comparison of arithmetic means using the INFOSTAT program and the valuation of percentages through EXCEL, comparisons were considered among the districts, and each one of the parameters studied. The results were: age of the first heat 18 months 46%; services by conception 1 service being 55%; type of services by conception (montage / insemination) an artificial insemination 34%; age at first delivery of 2 years 3 months 51%; interval among deliveries greater than 1 year 53%; open day from 1 to 3 months 68%; interval between jealousy from 15 to 25 days 77%; 24% have placental retention; they present dystocic birth 26%; animals that abort 19%; number of abortions per animal 1 abortion 78%; stage in which they abort with 32% in the 2 stage, body condition of 2 36%; feeding base alfalfa, ryegrass, oats and balanced 10%; deworming 95%; vaccination against reproductive diseases 26%; Requirement of veterinarian 60%. It is evident that the reproductive parameters of the mestizo cattle at Mulaló Parish are inefficient with the optimal reproductive parameters in cattle.